Pasar Islami Perspektif Santri - Ahmad Yunadi (LITERASI (Jurnal Ilmu Pendidikan), 2009)
Based on research finding, santris’ perspective toward market as the main role of economic which should conform syariah principles in order to get halal and toyyib profit. To create an Islamic market it is necessary to build Islamic markets or Islamize markets, in other words to fix the existing contract based on the syariah principles. In Islamic market, traders who do not understand syariah law are not allowed to enter the market. They can get training on syariah law, so can apply it on the market. Based on santris’ perspective, an Islamic market is not made based on whether or not there is rent and retribution fee. It is how the market does the transaction with syariah principles.  On santris’ perspective, exchange medium in Islamic market is not always dinar and dirham. It does not emphasize exchange medium but traders’ behavior whether they do the transaction based on syariah principles or not. Furthermore, using dinar or dirham does not guaranty no-usury because gold and silver belong to usury item. The most important thing is a role of hisbah council in watching market activities. They should watch the market and see how the transaction happened between traders.Keywords: market, Islam, Santri